The Intersectionality of African American Mothers in Counselor Education: A Phenomenological Examination. (March 2016) - Haskins, Natoya H.; Ziomek‐Daigle, Jolie; Sewell, Cheryl; Crumb, Lonika; Appling, Brandee; Trepal, Heather
Abstract : Using phenomenological inquiry, this study explored the lived experiences and intersecting identities of 8 African American counselor educators who are mothers. Six themes were identified: race, professional strain, work–life balance, support, internalized success, and mothering pedagogy.